Effective Harvesting of Nannochloropsis Microalgae Using Mushroom Chitosan: A Pilot-Scale Study - Chua, Elvis T.; Shekh, Ajam Y.; Eltanahy, Eladl; Thomas-Hall, Skye R.; Schenk, Peer M. (Frontiers in Bioengineering and Biotechnology, 2020)
For efficient downstream processing, harvesting remains as one of the challenges in producing Nannochloropsis biomass, a microalga with high-value omega-3 oils. Flocculation is an effective, low-energy, low-cost method to harvest microalgae. Chitosan has been shown to be an effective food-grade flocculant; however, commercial chitosan is sourced from crustaceans, which has disadvantages including concerns over heavy-metal contamination. Thus, this study tests the flocculation potential of mushroom chitosan. Our results indicate a 13% yield of chitosan from mushroom. The identity of the prepared chitosan was confirmed by Fourier-transform infrared spectroscopy. Furthermore, results show that mushroom chitosan can be an alternative flocculant with >95% flocculation efficiency when tested in 100-mL jar and 200-L vertical column photobioreactor. Applications in a 2000-L raceway pond demonstrated that thorough mixing of mushroom chitosan with the algal culture is required to achieve efficient flocculation. With proper mixing, mushroom chitosan can be used to produce food-grade Nannochloropsis biomass suitable for the production of vegan omega-3 oils as a fish oil alternative.